Comparison of transient interfacial tension behaviours of oil/alkaline systems as measured by the drop volume and spinning drop tensiometers. - Ball, Sheila D. (University of Ottawa (Canada), 1995)
The measurement of interfacial tension (IFT) as a function of time is useful for the study of reactions occurring at an interface. Reactions of particular importance occur in enhanced oil recovery (EOR) processes using alkaline flooding agents, in which injected alkaline solutions react with acidic oil trapped in the reservoir. In order to select the most effective alkaline agents available, an accurate method of measuring transient IFT is required. In this study, two methods of measuring the transient IFT have been examined. A relatively new method which uses an instrument called the drop volume tensiometer (DVT) has been studied. The results from this instrument have been compared to those obtained by the spinning drop tensiometer (SDT), which is the instrument most frequently used for studying transient IFT values. Interfacial tensions between oil and alkaline solutions were measured using the drop volume tensiometer and compared to those measured using the spinning drop tensiometer. The trend observed for the IFT as time progressed was surprisingly similar in both cases. However, the SDT values exhibited an increase in IFT after a minimum was reached whereas the DVT values did not generally exhibit this increase. The SDT appears to still be the preferred method for monitoring ultraflow IFT values (0.1 mN/m) as a function of time. However, it cannot be used to measure the IFT at the moment the oil droplet is created nor in the first 30 seconds once the two phases come into contact. In contrast, the DVT can only detect IFT at one discrete time. In addition, the DVT appeared to be able to measure IFT values below the manufacturer's stated lower limit of 0.2 mN/m, when employing highly viscous solutions, but was imprecise below this threshold level for solutions of lower viscosity. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.